ANALISIS EMISI CH4 DAN SERAPAN CO2 AKTIVITAS PERTANIAN DI JAWA TIMUR - Eko Murniyanto; Karuniawan Puji Wicaksono; Firman Farid Muhsoni (Universitas Trunojoyo Madura, 2011)
Agricultural activities contribute to the gases change in the air affecting adverse weather change, but on the other hand, it also cause the air reduction provides a profitable bioenergy. To learn these circumstances it is necessary to analyze the source and sink mainly CH4 and CO2. the scale of the analysis carried out within the wider administrative area so the results can be considered a basic policy. The results of analysis in East Java showed that CH4 emissions from rice fields since 2000 to 2010 has increased from 2,310,728 to 3,157,010 tons. At the same time, the rice field was able to reduce 51,902,504 tons and 70,916,580 tons CO2. The complexity of human activities and other gases in the air expect to result in weather changes which is indicated by rainfall increasing during the last decade.